The Analysis of Educational and Cultural Values of "Boho Oi Ndeu" in Wedding Ceremony of Bimanese at Rabakodo Village - Asbah Asbah (Linguistics and ELT Journal, 2017)
BohoOiNdeuis wedding ceremony to the bride and groom using coconut milk and water flowers inserted into the pottery(RoaBou), two bridal wear woven and tied using white thread(EroLanta)to the position of the body facing the Qiblah. It is intended that both partners in the wedding bond remain strong and lasting. The aim of this study to investigate Educational and Cultural values Boho Oi Ndeu in the wedding ceremony of Bimanese at Rabakodo village Bima Regency. The method of this study is a qualitative method and the data was collected used observation to informant, interviews informant to examine ceremony of Boho Oi Ndeu, and documentation to take pictures from an informant by using interviews and took videos while the ceremony of Boho Oi Ndeu was running. The results of this study showed that the Cultural values of the traditions of Boho Oi Ndeu performed by the ceremony are expected that the bride and groom would be lived in a harmonious family, happy, safe and peaceful. The Educational values during the ceremony of Boho Oi Ndeu get from a tool used by the nanny to bathe the bride and groom that consists of pottery, sarong, candles and white thread.